Developmental profile of ocular refraction in patients with congenital cataract: a prospective cohort study. (October 2016) - Liu, Zhenzhen; Long, Erping; Chen, Jingjing; Lin, Zhuoling; Lin, Duoru; Wu, Xiaohang; Cao, Qianzhong; Li, Xiaoyan; Wang, Dongni; Luo, Lixia; Qu, Bo; Liu, Runzhong; et al.
Abstract: Background: Refractive status is crucial to visual function and can change throughout life. For patients with congenital cataract, the developmental profile of refraction is complicated owing to the potential influence of diverse clinical manifestations and various treatments, and has not yet been fully characterised. Methods: In this prospective cohort study, we enrolled patients with congenital cataract from the Childhood Cataract Program of the Chinese Ministry of Health (CCPMOH). Two experienced cataract surgeons (YL and WC) did cataract removal or intraocular lens (IOL) implantation at Zhongshan Ophthalmic Center. Patients were followed up at 1 week, 1 month, and 3 months postoperatively, then every 3 months thereafter. Follow-up refraction assessments were conducted with objective retinoscopy and cycloplegia, and were performed by experienced independent optometrists. We compared refraction status (presented as spherical equivalent), and the rate of myopic shift between bilateral and unilateral congenital cataract with linear mixed model (LMM) analysis, then compared the range of myopic shift between bilateral and unilateral congenital cataract with multivariate linear regression Ethical approval was provided by the institutional review board of the Zhongshan Ophthalmic Center (Guangzhou, China). Parents of participating children provided written informed consent. Findings: Between Jan 1, 2010, and Oct 31, 2013, we enrolled 1258 participants, all of whom underwent cataract removal and/or intraocular lens (IOL) implantation. By study completion on Oct 31, 2015, 1164 (93%) participants had attended at least one follow-up visit and had refraction status recorded (6585 follow-ups total). Median follow-up was 3 years (IQR 2·5–4·5 years). Spherical equivalent measurements decreased by 1·36 D (SD 0·06) per year between 0·5 years and 4 years of age in bilateral and unilateral congenital cataract aphakic patients. The spherical equivalent of unilateral aphakia was 0·67 D (SD 0·31) smaller than that of bilateral aphakia after correcting for age and sex (p=0·0325). Spherical equivalents in congenital cataract pseudophakia decreased by 0·28 D (SD 0·02) between 1·5 years and 18 years of age (p<0·0001). Spherical equivalents in unilateral pseudophakia did not differ from bilateral pseudophakia (p=0·2996). With the current strategy for IOL calculation, the spherical equivalent in congenital cataract pseudophakia reached emmetropia around 6 years of age, while the healthy eyes of unilateral congenital cataract reached emmetropia at 9–10 years. The rate of myopic shift peaked in both young childhood and early adolescence in all participants. The range of myopic shift in the unilaterally congenital cataract affected eyes was correlated with age at refraction measurement, cataract removal, and IOL implantation, as well as with sex. Interpretation: Factors that dictate the range of myopic shift in unilateral congenital cataract seem to be different from those in bilateral congenital cataract, indicating differences in the aetiopathogenesis and refractive prognosis between bilateral and unilateral congenital cataract. Refraction data from patients with congenital cataract are of clinical significance to the guidelines for congenital cataract treatment, especially for IOL calculation concerning the laterality of congenital cataract. Funding: National Natural Science Foundation of China (number 81300750), the Ministry of Science and Technology of China Grants (973 program, 2015CB964600), the Key Research Plan for the National Natural Science Foundation of China (number 91546101) and the Guangdong Provincial Natural Science Foundation for Distinguished Young Scholars of China (number 2014A030306030).